Introduction of high-resolution anorectal manometry in Cuba. First outcomes - Vivianne Anido Escobar; Zunilda Díaz Drake; Tatiana Amable Díaz; Mildred Armenteros Torres; Maydolis Labrada Sosa; Jorge A, Ávila Anido (Revista Habanera de Ciencias Médicas, 2021)
Introduction: High-resolution anorectal manometry has allowed a better understanding of the pathophysiology of motor and sensory damage in patients with pelvic floor dysfunction.